Neuroinflammation as a pathophysiological factor in the development and maintenance of functional seizures: A hypothesis - Ayushe A. Sharma (Elsevier, 2021)
The neurobiological underpinnings of functional seizure (FS) development and maintenance represent an active research area. Recent work has focused on hardware (brain structure) and software (brain function and connectivity). However, understanding whether FS are an adaptive consequence of changes in brain structure, function, and/or connectivity is important for identifying a causative mechanism and for FS treatment and prevention. Further, investigation must also uncover what causes these structural and functional phenomena. Pioneering work in the field of psychoneuroimmunology has established a strong, consistent link between psychopathology, immune dysfunction, and brain structure/function. Based on this and recent FS biomarker findings, we propose a new etiologic model of FS pathophysiology. We hypothesize that early-life stressors cause neuroinflammatory and neuroendocrine changes that prime the brain for later FS development following secondary trauma (e.g., traumatic brain injury or psychological trauma). This framework coalesces existing knowledge regarding brain aberrations underlying FS and established neurobiological theories on the pathophysiology of underlying psychiatric disorders. We also propose brain temperature mapping as a way of indirectly visualizing neuroinflammation in patients with FS, particularly in emotion regulation, fear processing, and sensory-motor integration circuits. We offer a foundation on which future research can be built, with clear recommendations for future studies.